Beyond the fire of attrition: acid decay and forensic reconstruction - Craig-McFeely, J (Oxford University Press, 2023)
Digital images of manuscripts are primarily used today in much the same way as hardcopy research surrogates have been used since photography was introduced, allowing researchers to examine a manuscript page repeatedly and in detail without handling the book. This chapter explores the use of forensic musicology in the digital medium as a way of reconstructing lost manuscript content, focusing primarily on the Sadler Partbooks (Oxford, Bodleian Library MSS Mus. e. 1–5) as a case study. It examines the use of various surrogates as an aid to reconstructing a corpus. The chapter is both a case study and an introductory guide for those interested in the intersection of digital retrieval with archival and manuscript research.